Dorothee, a new genus of Cryptinae (Hymenoptera: Ichneumonidae) from Peru - Herrera-Flórez, Andrés Fabián (Zootaxa, 2021)
In this contribution, a new genus (and species) of Ceratocryptina (Hymenoptera: Ichneumonidae, Cryptinae, Cryptini): Dorothee panguanensis n. sp. is described from Peru. A diagnosis and an identification key to that subtribe of Cryptini are provided.